From real creators to real audiences: tracing the communication pathways of Chinese web series narratives - Zhang, Shangmingzhu; Hashim, Hasrul; Hassim, Nurzihan (Frontiers in Communication, 2025)
IntroductionThis study investigates how creators and audiences interact in shaping Chinese web series narratives, drawing on reception theory as a guiding framework. The aim is to trace communication pathways that influence narrative development and to examine how audience feedback shapes creative decisions.MethodsUsing qualitative methods, the research involved in-depth interviews with web series creators and viewers, followed by multi-level coding of the data.ResultsThe findings show that creators construct an “implied reader” to guide narrative design and adapt their storytelling in response to real-time audience reactions. This dynamic exchange marks a shift from one-way content delivery to a collaborative process of meaning-making.DiscussionThe study highlights the role of digital platforms in transforming narrative practices and provides insights into balancing artistic vision with market demands. These results contribute to a broader understanding of digital storytelling and offer practical implications for enhancing content creation and audience engagement in the evolving digital entertainment landscape.